2021
DOI: 10.1186/s12915-021-01031-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing sheds light on the contribution of structural variants to Brassica oleracea diversification

Abstract: Background Brassica oleracea includes several morphologically diverse, economically important vegetable crops, such as the cauliflower and cabbage. However, genetic variants, especially large structural variants (SVs), that underlie the extreme morphological diversity of B. oleracea remain largely unexplored. Results Here we present high-quality chromosome-scale genome assemblies for two B. oleracea morphotypes, cauliflower and cabbage. Direct comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 97 publications
(72 reference statements)
8
87
0
Order By: Relevance
“…As far as structural variation is concerned, their number and types were in general consistent with what has been reported in other plant species [ 29 , 30 ], although the use of different methods and parameters in different studies make them difficult to compare. Indeed, it is difficult to compare our results with other pepper genomes, since in resequencing projects, SVs were usually not annotated and discussed.…”
Section: Discussionsupporting
confidence: 78%
“…As far as structural variation is concerned, their number and types were in general consistent with what has been reported in other plant species [ 29 , 30 ], although the use of different methods and parameters in different studies make them difficult to compare. Indeed, it is difficult to compare our results with other pepper genomes, since in resequencing projects, SVs were usually not annotated and discussed.…”
Section: Discussionsupporting
confidence: 78%
“…Both summer/autumn and tropical broccoli and cauliflower also have only a weak vernalization requirement. In the SVD-quartets tree, Chinese kale is closest related to the cauliflowers and broccoli clades (AIL), which share the early flowering phenotype due to FLC mutations [ 18 ] but are characterized by more mutations (e.g. curd proliferation arrested inflorescence meristems).…”
Section: Discussionmentioning
confidence: 99%
“…Crisp (1982) hypothesized that cauliflowers are evolved from broccoli’s based on crossing experiments. In a recent study by Guo et al (2021), this was also suggested based on their inflorescence phenotypes and causal mutations [ 18 ]. Dale-Champ (1586) writes that cauliflowers have evolved between 400–600 BC and are believed to have diversified in the Eastern Mediterranean, and from there introduced to Italy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale structural variants can be detected using advanced third-generation sequencing methods and read mapping strategies such as high throughput chromosome conformation capture (Hi-C) and BioNano optical mapping technologies, as well as third-generation whole-genome sequencing strategies such as PacBio single-molecule real-time sequencing (SMRT) and Oxford Nanopore (ONT), which produce long reads and have been shown to overcome limitations on short reads to detect various SVs [131,132]. For example, in B. oleracea, large (100 kb or greater) SVs were detected using a combination of PacBio SMRT (DNA sequencing), PacBio Iso-Seq (RNA sequencing), BioNano optical mapping and Hi-C technologies [133], with genes related to stress response found to be related to these SVs. In B. napus, a 700 bp deletion of the V. longisporum resistance gene was identified using PacBio ONT sequencing [58].…”
Section: Genome Levelmentioning
confidence: 99%